Analysis of the Changes in Expression Levels of Sialic Acid on Influenza-Virus-Infected Cells Using Lectin-Tagged Polymeric Nanoparticles - Cho, Jaebum; Miyake, Yukari; Honda, Ayae; Kushiro, Keiichiro; Takai, Madoka (Frontiers in Microbiology, 2016)
Viral infections affect millions around the world, sometimes leading to severe consequences or even epidemics. Understanding the molecular dynamics during viral infections would provide crucial information for preventing or stopping the progress of infections. However, the current methods often involve the disruption of the infected cells or expensive and time-consuming procedures. In this study, fluorescent polymeric nanoparticles were fabricated and used as bioimaging nanoprobes that can monitor the progression of influenza viral infection through the changes in the expression levels of sialic acids expressed on the cell membrane. The nanoparticles were composed of a biocompatible monomer to prevent non-specific interactions, a hydrophobic monomer to form the core, a fluorescent monomer, and a protein-binding monomer to conjugate lectin, which binds sialic acids. It was shown that these lectin-tagged nanoparticles that specifically target sialic acids could track the changes in the expression levels of sialic acids caused by influenza viral infections in human lung epithelial cells. There was a sudden drop in the levels of sialic acid at the initial onset of virus infection (t = 0~1 hr) and at approximately 4~5 hrs post-infection. The latter drop correlated with the production of viral proteins that was confirmed using traditional techniques. Thus, the accuracy, the rapidity and the efficacy of the nanoprobes were demonstrated. Such molecular bioimaging tools, which allow easy-handling and in situ monitoring, would be useful to directly observe and decipher the viral infection mechanisms.